A two-dimensional CuCrSe2-CuCr2Se4 lateral magnetic heterojunction and a preparation method thereof
Patent Information
- Application Number
- CN202311076782.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-08-25
AI Technical Summary
两种相具备磁学研究潜力,但对于三元非层状材料,其气相合成较为困难
(1)该制备方法通过化学气相沉积法进行气相合成反应,采用套管空间限域的反应构型为体系提供了相对稳定的生长环境,更好控制前驱体的供应和载气的输运;根据两种金属源前驱体的熔点选择适当的生长温度,保证两种金属源同步蒸起并发生反应;调控前驱体质量比以得到结晶性良好的纯相CuCrSe2纳米片。
Smart Images

Figure CN117156956B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of nano-semiconductor materials, and more specifically, relates to a two-dimensional CuCrSe2-CuCr2Se4 lateral magnetic heterojunction and its preparation method. Background Technology
[0002] In 2017, researchers first verified the existence of two-dimensional ferromagnetism in two-dimensional Cr₂Ge₂Te₆, overturning the Mermin-Wagner theorem's assertion that two-dimensional long-range magnetic order does not exist under the isotropic Heisenberg model. Since then, layered van der Waals ferromagnetic two-dimensional materials such as CrI₃, Fe₃GeTe₂, and VSe₂ have been gradually discovered, and non-layered two-dimensional ferromagnetic nanosheets such as Cr₂Te₃ and Cr₅Te₈ have also been synthesized. The magnetism in ultrathin crystals provides opportunities for developing next-generation spintronic devices, such as non-volatile magnetic random access memory, spin valves, and magnetic tunnel junctions. Utilizing electron spin to achieve information transmission and storage, the emergence of two-dimensional ferromagnetic materials provides an ideal research platform for fundamental physics and next-generation spintronic devices and data storage devices.
[0003] Two-dimensional magnetic materials can form heterojunctions through vertical stacking or lateral bonding, providing a unique and extensive platform for exploring interfacial magnetic coupling effects. For example, the van der Waals spacing of a two-dimensional FePSe3-Fe3GeTe2 vertical heterostructure can be affected by external pressure, thereby modulating the exchange bias effect in the 2D magnetic heterostructure to achieve high-performance, robust memory applications. Two-dimensional lateral heterojunctions possess greater anisotropy and faster, stronger monolayer exchange coupling. Current research on two-dimensional magnetic heterojunctions mainly focuses on vertical heterojunction structures, with a lack of research on lateral heterojunction structures. This is due to the difficulty in synthesizing high-quality lateral magnetic heterojunctions.
[0004] Methods involving the mechanical exfoliation and transfer of two-dimensional materials can only yield vertical heterostructures, and often introduce defects and impurities into the interfacial gaps during the process, weakening interfacial coupling. Two-step CVD growth of heterojunctions is prone to surface passivation or atomic diffusion at the interface during the second growth step, making it difficult to obtain high-quality two-dimensional heterocrystalline structures. In contrast, one-step heterojunction growth avoids secondary exposure and heating issues, resulting in high-quality interfaces with atomic-level bonding. The fabrication of high-quality transverse magnetic heterojunctions is of great significance for exploring new magnetic phenomena.
[0005] CuCrSe2 is an antiferromagnetic nonlayered semiconductor belonging to the Fdm space group. Recently, an anomalous Hall effect of odd-even layers was discovered in two-dimensional CuCrSe2 nanosheets synthesized via vapor phase synthesis. CuCr2Se4, belonging to the R3m space group, has also been found to possess a high Curie temperature of 436 K in its two-dimensional nanosheets, making it a room-temperature ferromagnet. Both phases possess potential for magnetic research, but the vapor phase synthesis of ternary nonlayered materials is quite difficult. On the one hand, the increased degree of freedom of the elements leads to the synthesis of the ternary pure phase being affected by numerous interfering phases. On the other hand, the nonlayered structure results in chemical bonds in all directions, essentially hindering the anisotropic growth of two-dimensional materials. The vapor phase synthesis of ternary lateral heterojunctions is even more challenging, thus hindering the study of the magnetic properties of the heterojunction interface in ternary magnetic materials. Summary of the Invention
[0006] To address the aforementioned shortcomings or improvement needs of existing technologies, this invention provides a CuCrSe2-CuCr2Se4 lateral magnetic heterojunction and its preparation method. This method employs a sleeve-confined reaction configuration to provide a relatively stable growth environment. An appropriate growth temperature is selected based on the melting points of the two metal source precursors, and the precursor mass ratio is controlled to obtain pure-phase CuCrSe2 nanosheets. The sleeve-confined configuration provides a lower precursor flow rate and a stable growth environment, both restricting the out-of-plane growth of CuCrSe2. The degree of phase transformation can be controlled by adjusting the holding time, thereby synthesizing a high-quality, pure-phase two-dimensional CuCrSe2-CuCr2Se4 lateral magnetic heterojunction.
[0007] To achieve the above objectives, according to one aspect of the present invention, a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction and its preparation method are provided, the preparation method comprising the following steps: (1) Using copper iodide as the copper source and chromium powder mixed with potassium iodide as the chromium source, the copper source and the chromium source are placed in a quartz sleeve downstream of a single-temperature zone tube furnace; wherein the mass ratio of copper iodide, chromium powder and potassium iodide is (4 ~ 6): 1: 2. (2) Selenium powder is placed upstream of a single-temperature zone tubular furnace, and selenium vapor is carried downstream of the single-temperature zone tubular furnace by a carrier gas to react with the copper source and the chromium source; the reaction temperature is set to 840 ℃~ 860 ℃, and the holding time is 3~ 5 min to obtain a two-dimensional pure phase CuCrSe2 product. (3) After obtaining the two-dimensional pure phase CuCrSe2 product, extend the holding time to no more than 7 min to prepare the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction.
[0008] As a preferred embodiment of the present invention, the selenium powder is located 14 to 16 cm upstream of the tubular furnace from the center temperature zone.
[0009] As a preferred embodiment of the present invention, the selenium source is located upstream of the tubular furnace, at a distance of 14cm to 16cm from the center of the tubular furnace.
[0010] As a preferred embodiment of the present invention, the quartz sleeve is a cylindrical structure with one open end, the open end facing upstream of the single-temperature tube furnace; the tail of the quartz sleeve is located downstream of the tube furnace, 13 cm to 15 cm away from the center of the single-temperature tube furnace.
[0011] As a preferred embodiment of the present invention, the copper source is placed at a distance of 2 to 3.5 cm from the tail end of the quartz sleeve, and the chromium source is placed at a distance of 4 to 5 cm from the tail end of the quartz sleeve.
[0012] As a preferred embodiment of the present invention, the substrate is a fluorine-crystal mica sheet; the substrate is disposed above the chromium source.
[0013] As a preferred embodiment of the present invention, the carrier gas is argon and hydrogen, with the argon flow rate set to 200-250 sccm and the hydrogen flow rate set to 5-10 sccm.
[0014] As a preferred embodiment of the present invention, the internal pressure of the single-temperature zone tubular furnace is no greater than one atmosphere.
[0015] In a second aspect of the present invention, a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction is prepared based on the preparation method of the first aspect of the present invention.
[0016] In summary, compared with the prior art, the above-described technical solutions conceived by this invention mainly possess the following technical advantages: (1) The preparation method uses chemical vapor deposition to carry out gas phase synthesis reaction. The reaction configuration of the sleeve space confinement provides a relatively stable growth environment for the system, and better controls the supply of precursors and the transport of carrier gas. The appropriate growth temperature is selected according to the melting point of the two metal source precursors to ensure that the two metal sources evaporate and react simultaneously. The precursor mass ratio is adjusted to obtain pure phase CuCrSe2 nanosheets with good crystallinity.
[0017] The slow flow rate and stable growth environment mentioned above jointly limit the out-of-plane growth of CuCrSe2, ensuring the high-quality synthesis of two-dimensional CuCrSe2 nanosheets. Copper iodide can provide iodine vapor at high temperatures, thereby causing CuCrSe2 to undergo an in-situ phase transition to CuCr2Se4. By controlling the holding time, the degree of phase transition can be controlled, thus synthesizing high-quality, pure-phase two-dimensional CuCrSe2-CuCr2Se4 lateral magnetic heterojunctions.
[0018] (2) The present invention confines the reaction source in a quartz sleeve to ensure a stable and sufficient supply of various precursors, and suppresses the problem of uneven distribution of multi-metal precursors during long-distance transport, which leads to impurities in the final product.
[0019] (3) In this invention, metallic chromium powder is ground and mixed with potassium iodide as a chromium source. The choice of metallic source and potassium iodide is because the target ternary compound has a high synthesis temperature. Molten salt can react with metallic elements to generate corresponding iodides, thereby reducing the melting point of the metal source and increasing supersaturation. This reduces the required temperature while matching the vapor pressures of the two metal sources.
[0020] (4) This invention uses copper iodide powder as the copper source. On the one hand, compared with other copper sources (such as elemental copper and cuprous oxide), copper iodide has a lower melting point, providing a sufficient and stable copper source supply in the reaction. On the other hand, the iodine vapor generated by the decomposition of copper iodide at high temperature can react with the CuCrSe2 interlayer Cu. + The reaction causes Cu to form between the CuCrSe2 layers. + The copper nanosheets are extracted and transformed into a low-copper state, which then undergoes an in-situ phase transition at high temperature to form CuCr2Se4 crystalline material. The phase transition preferentially occurs at the edges of the CuCrSe2 nanosheets and gradually transitions inward. Within an appropriate growth time range, a CuCrSe2-CuCr2Se4 lateral magnetic heterostructure can be obtained. Furthermore, with extended growth time, CuCr2Se4 nanosheets with complete phase transition can also be obtained.
[0021] (5) The heat preservation time of the present invention is 3 to 8 mins. The heat preservation time is short and the energy consumption is low. At the same time, the formation process of the heterojunction can be precisely controlled by controlling the heat preservation time. Thus, the present invention can simultaneously realize the preparation of two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction and pure phase two-dimensional CuCrSe2 and CuCr2Se4 crystal materials.
[0022] (6) The two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared by this invention has a clear and distinct interface, and the two phases are pure and unetched; the transverse size can reach 20 μm, the thickness is uniform and the surface is without step undulations, and the thinnest sample is as thin as 9 nm; the diffraction spots are clear, and the high-resolution atomic images are free of distortion; the crystal quality is high. Magnetic force microscopy can clearly distinguish the two magnetic materials. The heterojunction interface has a higher magnetic signal than the ferromagnetic phase CuCr2Se4, which is attributed to the bias effect brought about by ferromagnetic and antiferromagnetic coupling.
[0023] (7) The two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure prepared by this invention provides a new approach for the study of interfacial magnetism and serves as an excellent carrier for researching spin-state modulation, interfacial coupling effects, and strong correlation effects. Simultaneously, it can provide material support for next-generation high-speed, low-power spin information technology, enabling more efficient information storage or processing devices. Attached Figure Description
[0024] Figure 1 A schematic diagram of the apparatus for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction provided in an embodiment of the present invention; Figure 2 This is an optical microscope image of the two-dimensional CuCrSe2 crystal material in Example 1 of the present invention; Figure 3 This is an optical microscope image of the two-dimensional CuCrSe2 crystal material in Embodiment 2 of the present invention; Figure 4 This is a mirror image of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction in Embodiment 3 of the present invention. Figure 5 This is a microscopic image of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction in Embodiment 4 of the present invention. Figure 6 This is an optical microscopic image of the two-dimensional CuCrSe2-CuCr2Se4 crystal material in Example 5 of the present invention; Figure 7 This is an optical microscopic image of the two-dimensional CuCr2Se4 crystal material in Example 6 of the present invention; Figure 8 The Raman curve of the two-dimensional CuCrSe2 crystal material in Example 2 of this invention; Figure 9 The Raman curve of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction in Embodiment 5 of the present invention; Figure 10 The Raman curve of the two-dimensional CuCr2Se4 crystal material in Example 6 of this invention; Figure 11This is a thickness measurement diagram of the two-dimensional CuCrSe2 crystal material prepared in Example 2 of the present invention; Figure 12 This is a thickness measurement image of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared in Example 5 of the present invention; Figure 13 This is a thickness measurement diagram of the two-dimensional CuCr2Se4 crystal material prepared in Example 6 of the present invention; Figure 14 The copper element composition analysis diagram of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared in Example 5 of the present invention; Figure 15 The chromium element composition analysis diagram of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared in Example 5 of the present invention is shown. Figure 16 This is a selenium element composition analysis diagram of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared in Example 5 of the present invention; Figure 17 This is a high-resolution atomic image of the CuCrSe2 phase of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure prepared in Example 5 of the present invention.
[0025] Figure 18 The electron diffraction pattern of the CuCrSe2 phase of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure prepared in Example 5 of the present invention.
[0026] Figure 19 This is a high-resolution atomic image of the CuCr2Se4 phase of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure prepared in Example 5 of the present invention.
[0027] Figure 20 The electron diffraction pattern of the CuCr2Se4 phase in the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure prepared in Example 5 of the present invention.
[0028] Figure 21 The magnetic phase signal diagram of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared in this invention.
[0029] In all the accompanying drawings, the same reference numerals are used to denote the same elements or structures, wherein: 1-Selenium powder, 2-Chromium source precursor, 3-Copper source precursor, 4-Quartz sleeve, 5-Mica substrate, 6-Ceramic boat. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The present invention provides a method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction, which uses a single-temperature zone horizontal tube furnace as the reaction device.
[0032] like Figure 1 The diagram shown is a schematic representation of the preparation apparatus according to an embodiment of the present invention. This single-temperature zone horizontal tube furnace is divided into upstream and downstream sections; the section closer to the left half of the furnace is the upstream section, and the section closer to the right half is the downstream section.
[0033] Where 1 represents the location of the selenium source. In actual experiments, the selenium source can be placed directly upstream of the tube furnace, or it can be loaded in a location such as a quartz boat or ceramic boat. The selenium source is located upstream of the tube furnace, 14 cm to 16 cm from the center of the tube furnace.
[0034] Among them, 2 is a chromium source precursor, 3 is a copper source precursor, 4 is a quartz sleeve, and 5 is a mica substrate. The substrate and both metal sources are placed inside the quartz sleeve. One end of the quartz sleeve is flat-bottomed and sealed, while the other end faces upstream. The inner and outer diameters are 11 mm and 13 mm, respectively, and the length is 7 cm. The tail of the sleeve is placed downstream of the tube furnace at a distance of 13 cm to 15 cm from the central temperature zone.
[0035] The copper source is placed 2–3.5 cm from the end of the quartz sleeve, and the chromium source is placed 4–5 cm from the end of the quartz sleeve. The copper and chromium sources are appropriately separated, and preferably the substrate is located above the chromium source, especially to the upper right.
[0036] Using the aforementioned single-temperature zone horizontal tube furnace as the reaction apparatus, the present invention provides a method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction, as follows: Figure 1 As shown, it includes the following steps: Selenium powder was placed in a porcelain boat 14-16 cm upstream from the center temperature zone, and the bottom of a quartz sleeve was placed downstream 13-15 cm from the center temperature zone. Copper iodide powder, elemental chromium, and potassium iodide powder were mixed and ground to obtain a precursor metal source, which was placed in the quartz sleeve at 2-3.5 cm and 4-5 cm from the sealed end, respectively. A mica enamel was placed upside down above and to the right of the chromium source.
[0037] During the reaction, the pressure inside the tube furnace is less than or equal to one atmosphere. The carrier gas is high-purity argon (99.9999% purity). Before the reaction, the reaction area is pre-evacuated, then argon is introduced, and the gas is repeatedly purged until all air is removed. The substrate is fluorinated mica. The carrier gas flow rate is maintained at 250 sccm throughout the reaction, and the hydrogen flow rate is 5 sccm.
[0038] The heating rate of the tube furnace was set to 50 ℃ / min, and the reaction temperature was controlled at 840 ℃~860 ℃. After reaching the above reaction temperature, the temperature was held for 3~5 min to allow the metal source and selenium source to diffuse and react on the mica substrate, initially generating two-dimensional CuCrSe2 crystal materials with triangular or hexagonal shapes. The reaction was continued for no more than 7 min, and the CuCrSe2 nanosheets were further reacted and transformed into CuCr2Se4 crystal materials at the edges, thus preparing a two-dimensional CuCrSe2-CuCr2Se4 lateral magnetic heterojunction with CuCrSe2 phase at the center and CuCr2Se4 phase at the edges. As the holding time was extended to 8 min or the temperature increased, the CuCrSe2 phase at the center of the heterojunction was also gradually transformed into CuCr2Se4 phase, generating pure CuCr2Se4 nanosheets.
[0039] The preparation method of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction provided by the present invention will be further described below with reference to specific embodiments.
[0040] The following are specific examples: Example 1 A single-temperature zone horizontal tube furnace was used as the reaction device. The horizontal tube furnace has a tube length of 90 cm, an outer diameter of 25 mm, a tube wall thickness of 2 mm, a constant temperature zone of 10 cm, a reaction temperature of 840 ℃, and a heating rate of 50 ℃ / min.
[0041] Copper iodide powder, chromium powder, and potassium iodide were weighed in a mass ratio of 4:1:2 and placed in a quartz sleeve, with a 5 mm gap between the copper iodide and the ground chromium powder. Freshly peeled fluorinated mica was placed upside down above the chromium source to the right, and then the quartz sleeve was placed 14 cm downstream of the tube furnace. 200 mg of selenium powder was weighed and placed in a ceramic boat as the selenium source, which was placed upstream of the tube furnace, 16 cm from the center of the single-temperature zone tube furnace.
[0042] Before the reaction, a pre-vacuum was applied to approximately 10 Pa, followed by the introduction of 600 sccm of Ar to atmospheric pressure, and repeated purging to remove residual oxygen. During the reaction, 250 sccm of Ar was introduced as a carrier gas, and the pressure was maintained at one atmosphere for 4 minutes. After the reaction, the carrier gas remained unchanged, and the product was rapidly cooled to room temperature, yielding a two-dimensional CuCrSe2 crystal material from the fluorinated mica sheet.
[0043] Example 2 A single-temperature zone horizontal tube furnace was used as the reaction device. The horizontal tube furnace has a tube length of 90 cm, an outer diameter of 25 mm, a tube wall thickness of 2 mm, a constant temperature zone of 10 cm, a reaction temperature of 840 ℃, and a heating rate of 50 ℃ / min.
[0044] Copper iodide powder, chromium powder, and potassium iodide in a mass ratio of 6:1:2 were weighed and placed in a quartz sleeve, with a 1 cm gap between the copper iodide and the ground chromium powder. Freshly peeled fluorinated mica was placed upside down above the chromium source to the right, and then the quartz sleeve was placed 14 cm downstream of the tube furnace. 200 mg of selenium powder was weighed and placed in a ceramic boat as the selenium source, which was placed upstream of the tube furnace, 16 cm from the center of the single-temperature zone tube furnace.
[0045] Before the reaction, a pre-vacuum was applied to approximately 10 Pa, followed by the introduction of 600 sccm of Ar to atmospheric pressure, and repeated purging to remove residual oxygen. During the reaction, 250 sccm of Ar was introduced as a carrier gas, and the pressure was maintained at one atmosphere for 4 minutes. After the reaction, the carrier gas remained unchanged, and the product was rapidly cooled to room temperature, yielding a two-dimensional CuCrSe2 crystal material from fluorinated mica sheets.
[0046] Example 3 A single-temperature zone horizontal tube furnace was used as the reaction device. The horizontal tube furnace has a tube length of 90 cm, an outer diameter of 25 mm, a tube wall thickness of 2 mm, a constant temperature zone of 10 cm, a reaction temperature of 840℃, and a heating rate of 50 ℃ / min.
[0047] Copper iodide powder, chromium powder, and potassium iodide in a mass ratio of 6:1:2 were weighed and placed in a quartz sleeve, with a 1 cm gap between the copper iodide and the ground chromium powder. Freshly peeled fluorinated mica was placed upside down above the chromium source to the right, and then the quartz sleeve was placed 14 cm downstream of the tube furnace. 200 mg of selenium powder was weighed and placed in a ceramic boat as the selenium source, which was placed upstream of the tube furnace, 16 cm from the center of the single-temperature zone tube furnace.
[0048] Before the reaction, a pre-vacuum was applied to approximately 10 Pa, followed by the introduction of 600 sccm of Ar to atmospheric pressure, and repeated purging to remove residual oxygen. During the reaction, 250 sccm of Ar was introduced as the carrier gas, and the pressure was maintained at one atmosphere for 5 minutes. After the reaction, the carrier gas remained unchanged, and the product was rapidly cooled to room temperature, yielding a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure on a fluorinated mica sheet.
[0049] Example 4 A single-temperature zone horizontal tube furnace was used as the reaction device. The horizontal tube furnace has a tube length of 90 cm, an outer diameter of 25 mm, a tube wall thickness of 2 mm, a constant temperature zone of 10 cm, a reaction temperature of 840 ℃, and a heating rate of 50 ℃ / min.
[0050] Copper iodide powder, chromium powder, and potassium iodide in a mass ratio of 6:1:2 were weighed and placed in a quartz sleeve, with a 1 cm gap between the copper iodide and the ground chromium powder. Freshly peeled fluorinated mica was placed upside down above the chromium source to the right, and then the quartz sleeve was placed 14 cm downstream of the tube furnace. 200 mg of selenium powder was weighed and placed in a ceramic boat as the selenium source, which was placed upstream of the tube furnace, 16 cm from the center of the single-temperature zone tube furnace.
[0051] Before the reaction, a pre-vacuum was applied to approximately 10 Pa, followed by the introduction of 600 sccm of Ar to atmospheric pressure, and repeated purging to remove residual oxygen. During the reaction, 250 sccm of Ar was introduced as the carrier gas, and the pressure was maintained at one atmosphere for 6 mins. After the reaction, the carrier gas remained unchanged, and the product was rapidly cooled to room temperature, yielding a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure on a fluorinated mica sheet.
[0052] Example 5 A single-temperature zone horizontal tube furnace was used as the reaction device. The horizontal tube furnace has a tube length of 90 cm, an outer diameter of 25 mm, a tube wall thickness of 2 mm, a constant temperature zone of 10 cm, a reaction temperature of 840 ℃, and a heating rate of 50 ℃ / min.
[0053] Copper iodide powder, chromium powder, and potassium iodide in a mass ratio of 6:1:2 were weighed and placed in a quartz sleeve, with a 1 cm gap between the copper iodide and the ground chromium powder. Freshly peeled fluorinated mica was placed upside down above the chromium source to the right, and then the quartz sleeve was placed 14 cm downstream of the tube furnace. 200 mg of selenium powder was weighed and placed in a ceramic boat as the selenium source, which was placed upstream of the tube furnace, 16 cm from the center of the single-temperature zone tube furnace.
[0054] Before the reaction, a pre-vacuum was applied to approximately 10 Pa, followed by the introduction of 600 sccm of Ar to atmospheric pressure, and repeated purging to remove residual oxygen. During the reaction, 250 sccm of Ar was introduced as the carrier gas, and the pressure was maintained at one atmosphere for 7 minutes. After the reaction, the carrier gas remained unchanged, and the product was rapidly cooled to room temperature, yielding a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterostructure on a fluorinated mica sheet.
[0055] Example 6 A single-temperature zone horizontal tube furnace was used as the reaction device. The horizontal tube furnace has a tube length of 90 cm, an outer diameter of 25 mm, a tube wall thickness of 2 mm, a constant temperature zone of 10 cm, a reaction temperature of 840 ℃, and a heating rate of 50 ℃ / min.
[0056] Copper iodide powder, chromium powder, and potassium iodide in a mass ratio of 6:1:2 were weighed and placed in a quartz sleeve, with a 1 cm gap between the copper iodide and the ground chromium powder. Freshly peeled fluorinated mica was placed upside down above the chromium source to the right, and then the quartz sleeve was placed 14 cm downstream of the tube furnace. 200 mg of selenium powder was weighed and placed in a ceramic boat as the selenium source, which was placed upstream of the tube furnace, 16 cm from the center of the single-temperature zone tube furnace.
[0057] Before the reaction, a pre-vacuum was applied to approximately 10 Pa, followed by the introduction of 600 sccm of Ar to atmospheric pressure, and repeated purging to remove residual oxygen. During the reaction, 250 sccm of Ar was introduced as a carrier gas, and the pressure was maintained at one atmosphere for 8 minutes. After the reaction, the carrier gas remained unchanged, and the product was rapidly cooled to room temperature, yielding a two-dimensional CuCr2Se4 crystal material from fluorinated mica sheets.
[0058] The materials prepared in the above embodiments were tested, and the test results and analysis are as follows: The surface morphology of the two-dimensional CuCrSe2, CuCrSe2-CuCr2Se4 lateral magnetic heterojunctions, and CuCr2Se4 crystal materials prepared in Examples 1-6 was characterized using an optical microscope. The results are as follows: Figures 2-7 As shown.
[0059] from Figures 2-7 It can be seen that in Examples 1 and 2, when the reactor temperature is 840 ℃ and the holding time is 4 min, the results are as follows: Figure 2 and Figure 3 As shown, the product is CuCrSe2 pure-phase nanosheets; in Examples 3, 4, and 5, when the holding time was 5-7 min, the results were as follows: Figure 4 , Figure 5 and Figure 6As shown, the product is a CuCrSe2-CuCr2Se4 transverse magnetic heterojunction; in Example 6, when the holding time was 8 min, as... Figure 7 As shown, the product is a pure-phase CuCr2Se4 nanosheet. These results demonstrate that we can control the phase transformation ratio from CuCrSe2 to CuCr2Se4 by controlling the holding time, thereby achieving the preparation of a controllable CuCrSe2-CuCr2Se4 lateral magnetic heterojunction.
[0060] The two-dimensional CuCrSe2, CuCrSe2-CuCr2Se4 lateral magnetic heterojunction, and CuCr2Se4 crystal material prepared in Examples 2, 5, and 6 were characterized using confocal Raman optical microscopy. Figure 8 Raman spectroscopy of the CuCrSe2 material prepared in Example 2 showed characteristic peaks of CuCrSe2. Figure 9 The transverse magnetic heterojunction prepared in Example 5 has an outer CuCr2Se4 phase and an inner CuCrSe2 phase. Figure 10 The Raman spectroscopy results of the material prepared in Example 6 showed characteristic peaks of CuCr2Se4.
[0061] The thickness of the materials prepared in Examples 2, 5, and 6 was measured using an atomic force microscope probe to scan the sample surface. Figure 11 The thickness measurement diagram of the CuCrSe2 crystal material in Example 2 shows that the thickness of the nanosheets prepared in Example 2 is 10.6 nm. Figure 12 The thickness measurement diagram of the CuCrSe2-CuCr2Se4 transverse magnetic heterojunction in Example 5 shows that the thickness of the nanosheet prepared in Example 5 is 8.85 nm. Figure 13 The thickness measurement diagram corresponding to the CuCr2Se4 crystal material in Example 6 shows that the thickness of the nanosheets prepared in Example 6 is 8.4 nm.
[0062] Elemental composition analysis of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared in Example 5 was performed using energy-dispersive X-ray spectroscopy. The results are shown in [Figure number missing]. Figures 14-16 CuCrSe2 has a higher copper content than CuCr2Se4, and chromium and selenium are evenly distributed in both phases.
[0063] The crystal structures of the materials prepared in Examples 2, 5, and 6 were characterized using transmission electron microscopy. Figure 17 This is a high-resolution lattice image of CuCrSe2. Figure 18 The corresponding electron diffraction pattern is shown below. Figure 19 This is a high-resolution lattice image of CuCr2Se4. Figure 20 For the corresponding electron diffraction pattern, combined Figure 17 ~20 confirms that the product is a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction.
[0064] The magnetic signal of the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared in Example 5 was detected using a magnetic force microscope. The results are as follows: Figure 21 As shown, the magnetic domain structure of the ferromagnetic phase CuCr2Se4 and the high magnetic signal at the heterojunction interface were measured, while the net magnetic moment of the antiferromagnetic CuCrSe2 phase was zero, exhibiting the same contrast as the substrate. The high magnetic signal at the interface may originate from the exchange bias effect generated by the strong coupling interface of the antiferromagnetic / ferromagnetic lateral heterojunction.
[0065] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction, characterized in that, Includes the following steps: (1) Using copper iodide as the copper source and chromium powder mixed with potassium iodide as the chromium source, the copper source and the chromium source are placed in a quartz sleeve downstream of a single-temperature zone tube furnace; wherein, the mass ratio of copper iodide, chromium powder and potassium iodide is (4~6): 1:2; the quartz sleeve is a cylindrical structure with one open end, and the open end faces upstream of the single-temperature zone tube furnace; (2) Selenium powder is placed upstream of a single-temperature zone tubular furnace, and selenium vapor is carried downstream of the single-temperature zone tubular furnace by a carrier gas to react with the copper source and the chromium source; the reaction temperature is set to 840 ℃ ~ 860 ℃, and the holding time is 3 ~ 4 min to obtain a two-dimensional pure phase CuCrSe2 product. (3) After obtaining the two-dimensional pure phase CuCrSe2 product, the heat preservation time is extended to no more than 7 min to prepare the two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction.
2. The method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction according to claim 1, characterized in that, The selenium source is located upstream of the tubular furnace, at a distance of 14 cm to 16 cm from the center of the tubular furnace.
3. The method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction according to claim 1, characterized in that, The tail of the quartz sleeve is located downstream of the tubular furnace, 13 cm to 15 cm from the center of the single-temperature zone tubular furnace.
4. The method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction according to claim 1, characterized in that, The copper source is placed 2 to 3.5 cm from the end of the quartz sleeve, and the chromium source is placed 4 to 5 cm from the end of the quartz sleeve.
5. The method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction according to any one of claims 1-4, characterized in that, The substrate is a fluorine-crystalline mica sheet; the substrate is disposed above the chromium source.
6. The method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction according to claim 1, wherein the carrier gas is argon and hydrogen, the argon flow rate is set to 200-250 sccm, and the hydrogen flow rate is set to 5-10 sccm.
7. The method for preparing a two-dimensional CuCrSe2-CuCr2Se4 transverse magnetic heterojunction according to claim 1, characterized in that, The internal pressure of the single-temperature zone tubular furnace is no greater than one atmosphere.
8. The CuCrSe2-CuCr2Se4 transverse magnetic heterojunction prepared by the preparation method according to any one of claims 1-7.
Citation Information
Patent Citations
Preparation method of two-dimensional In2S3 / SnS heterojunction crystal material
CN112663144A
Two-dimensional CuCrS2 crystal material and preparation method thereof
CN114197036A